The Impact of Targeted Therapies on Red Blood Cell Aggregation in Patients with Chronic Lymphocytic Leukemia Evaluated Using Software Image Flow Analysis - Anika Alexandrova-Watanabe; Emilia Abadjieva; Lidia Gartcheva; Ariana Langari; Miroslava Ivanova; Margarita Guenova; Tihomir Tiankov; Velichka Strijkova; Sashka Krumova; Svetla Todinova (Micromachines)
Chronic lymphocytic leukemia (CLL), the most common type of leukemia, remains incurable with conventional therapy. Despite advances in therapies targeting Bruton’s tyrosine kinase and anti-apoptotic protein BCL-2, little is known about their effect on red blood cell (RBC) aggregation in blood flow. In this study, we applied a microfluidic device and a newly developed Software Image Flow Analysis to assess the extent of RBC aggregation in CLL patients and to elucidate the hemorheological effects of the commonly applied therapeutics Obinutuzumab/Venetoclax and Ibrutinib. The results revealed that, in RBC samples from untreated CLL patients, complex 3D clusters of large RBC aggregates are formed, and their number is significantly increased compared to healthy control samples. The application of the Obinutuzumab/Venetoclax combination did not affect this aspect of RBCs’ rheological behavior. In contrast, targeted therapy with Ibrutinib preserves the aggregation state of CLL RBCs to levels seen in healthy controls, demonstrating that Ibrutinib mitigates the alterations in the rheological properties of RBCs associated with CLL. Our findings highlight the alterations in RBC aggregation in CLL and the impact of different targeted therapies on RBCs’ rheological properties, which is critical for predicting the potential complications and side effects of CLL treatments, particularly concerning blood flow dynamics.